Preliminary studies on mining methods used in sivand quarries during the achaemenian period in fars province, iran (2010)
Ancient civilizations all around the world, from China, Iran, Mesopotamia, Egypt and Greece to South America, have attracted archaeologist’s and historian’s notice for their cultures as well as their techniques they used for extracting natural resources. The palaces, chambers, temples, and tombs demonstrate the advanced engineering technologies that known at that times. Archaeology based geological methods and observations, help scientists to find evidences towards the techniques that ancient people used to provide the raw materials for creating their enormous structures. Discovering the compatibility of materials used for constructing buildings or temples has resulted in a revival of stone cutting methods and their processing’s technology. The enormous blocks of stones which were excavated from a mountain had to be prepared suitably for superior usage in such building complexes as Persepolis (Takht-e Djamshid, 600 – 400 BC). Apart from them, one should also consider the preparation process, its influence and the quality of the blocks. This paper reviews the status of the Sivand quarries in the Fars province of Iran with respect to their technical and mineralogical data. The quality of material from these mines as well as the unique similarities between these rocks and those which were used in Persepolis, suggest them to be one of the raw sources which used for Persepolis complex.